Evaluation of Prospective Bride Screening Policy Implementation in Dolo District Areas 2025 - Rizka Rizka; Sudirman Sudirman; Abdul Kadri (Universitas Ibn Khaldun Bogor, 2026)
The screening policy for prospective brides and grooms is a strategic intervention to prevent stunting from upstream. This research aims to evaluate the implementation of the prospective bride and groom screening policy in Dolo District, Sigi Regency, in 2025. The research uses a qualitative approach with a case study design. Data was collected through in-depth interviews, observation and documentation. The informants were determined purposively, consisting of 11 people including Community Health Center officers, KUA, cadres, and prospective brides and grooms. Analysis uses the Miles & Huberman model. The research results show that policy implementation is not optimal. The six variables of the Van Meter & Van Horn model are the main findings: (1) policy standards experience a reduction in meaning to administrative formality; (2) resources experience systemic deficits in medical logistics and budget; (3) the characteristics of implementing agents are characterized by procedural informality without local SOPs; (4) the implementer's attitude is positive but the workload is pressured; (5) fragmented interorganizational communications without fixed protocols; (6) socio-cultural conditions in the form of